2014
DOI: 10.1603/me14083
|View full text |Cite
|
Sign up to set email alerts
|

Use of Insecticide Delivery Tubes for Controlling Rodent-Associated Fleas in a Plague Endemic Region of West Nile, Uganda

Abstract: Plague is a primarily flea-borne rodent-associated zoonosis that is often fatal in humans. Our study focused on the plague-endemic West Nile region of Uganda where affordable means for the prevention of human plague are currently lacking. Traditional hut construction and food storage practices hinder rodent exclusion efforts, and emphasize the need for an inexpensive but effective host-targeted approach for controlling fleas within the domestic environment. Here we demonstrate the ability of an insecticide del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…(S1 Table). This observation was consistent with a previous study where the treatment devices were visited equally over the study [37]. If the bait stations were constantly visited, the observation of tracks or bait consumption could not generate important information related to the percentage of resident rodent actually visiting the bait station per night.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(S1 Table). This observation was consistent with a previous study where the treatment devices were visited equally over the study [37]. If the bait stations were constantly visited, the observation of tracks or bait consumption could not generate important information related to the percentage of resident rodent actually visiting the bait station per night.…”
Section: Discussionsupporting
confidence: 89%
“…One reason may be a lack of coverage, more likely at the room level than the house level. A study demonstrated that the success of the insecticide delivery tube technique targeting fleas harbored by commensal rat depended on the placement of the device directly on rat runway, in a single room household [37]. In addition, monitoring rat movement in a single-room household scale probably facilitated the implementation of the technique, conversely to multiple-story house.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of insecticide dusting in household, the quantity of insecticide is reduced because the insecticide bait box is more focused on fleas harbored by rodent with the host acting as a vehicle for the insecticide, carrying it to its nest. In the same line of thought, the feasibility of “insecticide delivery tubes” in reducing flea loads was studied on commensal rodents, capitalizing on the knowledge of their behavior [ 56 ]. Similarly, using rodent bait containing systemic insecticide could be a new avenue for combating or at least, reducing fleas load on rodents in plague endemic area during inter-epidemic season [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although IRS is effective against on-host fleas, the costs of such interventions can be significant when supplies, training, and transportation are included. 12 More cost-effective methods of flea control, such as topical insecticide rodent tubes 11 may provide an alternate strategy. Given sufficient residual activity, this or other similar low-cost interventions could be deployed before the start of the plague season to reduce the risk of infectious flea bites or within the current program in response to rodent die offs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies from the West Nile region have shown that indoor residual spraying (IRS) and insecticide delivery tubes effectively reduce flea loads on rodents in the home environment where most exposures are believed to occur. 6 , 11 , 12 While most households in a 2013 study self-reported using some form of rodent control, such as lethal trapping, application of rodenticide, or cat ownership; 13 thus far, rodent control, specifically the use of poisons, or traps, have not proven to be effective given the massive resources required to sustain suppression of populations. 14 Secondary prevention of plague aims to reduce case fatality rates through education campaigns that emphasize recognition of signs of plague and urging persons with symptoms consistent with plague to seek care without delay.…”
mentioning
confidence: 99%